(untitled) (Revista Lusófona de Educação, 2026)
Educating monitors-tutors for academic literacy in focus: dialogue between different ‘generations’ and experiences as tools for professional development Abstract: In this article, we will present the analysis of data generated by two interviews with experts, in order to show how dialogue between different ‘generations’ of senior researchers and monitor-tutors, based on knowledge gained from experience, can have an impact on professional development and increase their power to act (Clot, 2008). Based on two branches of work sciences, Clinic Activity (Clot et al, 2000) and Activity Ergonomics (Faïta, 2004), and on Sociodiscursive Interactionism (Bronckart, 1996), of Vygotskian orientation (Vygotski, 1985), two Brazilian academic literacy laboratories have initiated an educational process that proposes that senior researchers interact with monitor-tutors in order to contribute to the professional development of less experienced researchers by sharing knowledge to and for teaching (Hofstetter; Schneuwly, 2009). The two interviews were conducted by two monitor-tutors with two senior researchers in the fields of Education and Applied Linguistics on how to write a scientific article. The results indicate that, through interview methods with an expert, senior professional, students confront and discuss ways of producing scientific articles, reflecting on different ways of acting, with the possibility of selecting and appropriating knowledge that can contribute to their own actions. By promoting this educational structure, a dialogue was established between different generations of teachers and monitor-tutors, thus contributing to the expansion of the repertoire of possibilities for action by monitor-tutors, which will certainly affect the education of the students they will serve in literacy laboratories and even in their classrooms as teachers in the future. Keywords: Professional Development. Intergenerational dialogues. Education. Academic Literacy. Power to act.